Marketing Mix on the Decision to Subscribe to Netflix Video Streaming Services in Thailand - Sanpinit, Papitchaya; Tantrabundit, Pongsatorn (Journal for Developing the Social and Community, 2026)
Background and Objectives: This independent study focuses on analyzing the subscription decision-making process of Netflix users in Thailand. The primary objectives are to examine the influence of service usage behaviors on the decision-making process, investigate the relationship between the service marketing mix and subscription decisions, and identify the specific dimensions of the marketing mix (7Ps) that significantly influence the adoption of Netflix video streaming services among Thai consumers. Methodology: A quantitative research approach was employed, with data collected via questionnaires from a sample of 400 consumers in Thailand who had prior experience with the Netflix platform. The data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. Inferential statistics used for hypothesis testing included Pearson’s Correlation Coefficient and Multiple Regression Analysis. Results: Regarding consumer behavior, the study found that differences in service usage behaviors did not result in a statistically significant difference in the overall subscription decision-making process at the 0.05 level. In terms of correlation, the service marketing mix factors exhibited a strong positive correlation with the decision to subscribe to Netflix at a 0.01 significance level, with correlation coefficients (r) ranging between 0.677 and 0.922. Conclusion: The analysis identifies five specific dimensions of the Service Marketing Mix—Product, Price, Place, Promotion, and Process—as key factors significantly influencing the subscription decision for video streaming services in Thailand. These independent variables collectively explain 96.1% (R^2 = 0.961) of the variance in the subscription decision (Adoption), with statistical significance at the 0.05 level.